Thickness measurement of low-Z films fabricated on thick substrate using EDXRF technique. (January 2021) - Upmanyu, Arun Kumar; Kailash; Kapil, Ashutosh; Mehta, D.; Kumar, Sanjeev
Abstract: The present work reports a method for thickness measurements of low-Z films deposited on a thick substrate using energy dispersive X-ray fluorescence (EDXRF) technique. For this, ZnO and single-wall carbon nanotubes (SWCNTs) films (thickness ~ 1–100 mm) were fabricated on thick Si substrates using a sol-gel spin coating technique. The fabricated films were characterized using X-ray diffraction (XRD) and atomic force microscope (AFM) measurements. The thicknesses of fabricated films were determined from the measured attenuation of Si -Kαβ characteristics X-rays emitted from the thick Si substrate in coated materials. The thick substrate was excited by Mn Kα (5.895 keV) and Kβ (6.492 keV) X-rays obtained from annular 55Fe radioactive source in reflection mode geometrical setup. The emitted characteristics X-rays were detected by a low energy Ge (LEGe) detector coupled with PC based multichannel analyzer. The obtained results show good agreement with the values obtained from well-established X-ray fluorescence (XRF) and atomic force microscopy (AFM) measurements. The experimental results recommend the use of reported methodology for thickness measurement of low-Z materials deposited on a thick substrate for material characterization in future. Highlights: ZnO and single-wall carbon nanotubes (SWCNTs) thin films were fabricated on thick Si substrates. Fabricated films were characterized using XRD and AFM measurements. The thicknesses of fabricated films were determined by attenuation method using EDXRF technique. Reported methodology can be used in material characterization in futureReported methodology can be used in material characterization in future.